Successful Treatment of a Critically Ill COVID-19 Patient Using Continuous Renal Replacement Therapy With Enhanced Cytokine Removal and Tocilizumab: A Case Report - Huang, Thomas Tao-Min; Chien, Ying-Chun; Wang, Chih-Hsien; Chang, Sui-Yuan; Wang, Jann-Tay; Hsieh, Song-Chou; Yeh, Yu-Chang; Ku, Shih-Chi; Yu, Chong-Jen; Chiang, Bor-Luen; Chang, Shan-Chwen; Tolwani, Ashita (Frontiers in Medicine, 2021)
Coronavirus disease (COVID-19) pandemic has caused worldwide mortality. There are no effective treatments available currently. The most severe patients need sustained-life support for recovery. We herein report a critically ill COVID-19 patient with multi-organ failure, including acute respiratory failure, acute renal failure, and fulminant cytokine release syndrome (CRS), who required mechanical ventilation and extracorporeal membrane oxygenation support. By means of delicate oxygenation support, uremic toxin removal, and hemodynamic support, and most importantly, cytokine-targeted intervention for CRS, including cytokine/endotoxin removal, anti-cytokine therapy, and immune modulation, we successfully treated the patient with a predicted high mortality risk. Comprehensive cytokine data, CRS parameters, and biochemical data of extracorporeal removal were provided to strengthen the rationale of this strategy. In this report, we demonstrated that timely combined hemoperfusion with cytokine adsorptive capacity and anti-cytokine therapy can successfully treat COVID-19 patients with fulminant CRS. It also highlights the importance of implementing cytokine-targeted therapy for severe COVID-19 guided by the precise measurement of disease activity.